2013
DOI: 10.1115/1.4023524
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Specific Inverse Dynamics of the Head and Cervical Spine During in Vivo Dynamic Flexion-Extension

Abstract: The effects of degeneration and surgery on cervical spine mechanics are commonly evaluated through in vitro testing and finite element models derived from these tests. The objectives of the current study were to estimate the load applied to the C2 vertebra during in vivo functional flexion-extension and to evaluate the effects of anterior cervical arthrodesis on spine kinetics. Spine and head kinematics from 16 subjects (six arthrodesis patients and ten asymptomatic controls) were determined during functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Future studies are necessary to assess the kinematic results (bone kinematics and tissue-level kinematics) when imaging static and dynamic activities, and to assess the effect of movement direction on kinematics in other joints. Third, considering the fact that musculoskeletal models of the head and cervical spine assume the active muscles are determined by head angle, not movement direction (Anderst et al, 2013, in press; Liu et al., 2007), the current results suggest that these models should account for the direction of head motion when determining muscle moment arms because vertebral orientations (and therefore muscle attachment sites) are dependent on the direction of head motion. The direction-dependent differences at each motion segment are cumulative, leading to substantially different spine configurations for identical head orientations when moving in flexion or extension.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Future studies are necessary to assess the kinematic results (bone kinematics and tissue-level kinematics) when imaging static and dynamic activities, and to assess the effect of movement direction on kinematics in other joints. Third, considering the fact that musculoskeletal models of the head and cervical spine assume the active muscles are determined by head angle, not movement direction (Anderst et al, 2013, in press; Liu et al., 2007), the current results suggest that these models should account for the direction of head motion when determining muscle moment arms because vertebral orientations (and therefore muscle attachment sites) are dependent on the direction of head motion. The direction-dependent differences at each motion segment are cumulative, leading to substantially different spine configurations for identical head orientations when moving in flexion or extension.…”
Section: Discussionmentioning
confidence: 88%
“…In order to address these limitations associated with static imaging of the spine, imaging during dynamic, functional motion has become more common (Anderst et al, 2013, in press; McDonald et al, 2010; Reitman et al, 2004; van Mameren et al, 1992; Wu et al, 2010). Previous dynamic imaging studies of the cervical spine have focused entirely on intervertebral kinematics while neglecting to investigate the relationship between head motion and intervertebral motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). This novel imaging and tracking technology has recently been combined with custom computational algorithms to characterize cervical spine mechanics in young healthy adults, in middle‐aged asymptomatic adults and arthrodesis patients, and in arthrodesis and arthroplasty patients …”
Section: Advances In Technologymentioning
confidence: 99%
“…Using radiographic images collected continuously during the dynamic movement, dynamic biplane radiography has demonstrated that, in the sub‐axial cervical spine of asymptomatic subjects, mid‐range flexion/extension is dominated by C3/C4 and C4/C5 motion, while contributions from C5/C6, and C6/C7 motion segments increase near the start, and the end of the full ROM, when loads on the spine are greatest (Fig. B).…”
Section: Cervical Spine Kinematicsmentioning
confidence: 99%